Efficient photocatalytic proton-coupled electron-transfer reduction of O2 using a saddle-distorted porphyrin as a photocatalyst. Issue 34 (10th April 2019) - Aoki, Emi; Suzuki, Wataru; Kotani, Hiroaki; Ishizuka, Tomoya; Sakai, Hayato; Hasobe, Taku; Kojima, Takahiko
Abstract : Photocatalytic O2 reduction reactions proceeded efficiently to produce H2 O2 using a diprotonated saddle-distorted dodecaphenylporphyrin as a photocatalyst. Abstract : Photocatalytic O2 reduction reactions proceeded to produce H2 O2 using a diprotonated saddle-distorted dodecaphenylporphyrin as a photocatalyst. The quantum yield (12%), the turnover number (3000 for 6 h), and the turnover frequency (500 h −1 ) are achieved in photocatalytic systems based on free-base porphyrins for the first time. The photocatalytic reaction mechanism has been revealed by ns-laser flash photolysis and kinetic analysis.